2020
DOI: 10.1371/journal.pone.0232423
|View full text |Cite
|
Sign up to set email alerts
|

A mixed-methods assessment of disclosure of HIV status among expert mothers living with HIV in rural Nigeria

Abstract: Background Peer support provided by experienced and/or trained "expert" women living with HIV has been adopted by prevention of mother-to-child transmission of HIV (PMTCT) programs across sub-Saharan Africa. While there is ample data on HIV status disclosure among nonexpert women, there is little data on disclosure among such expert women, who support other women living with HIV. Objective This study compared HIV disclosure rates between expert and non-expert mothers living with HIV, and contextualized quantit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Early studies have generally shown high acceptability of text messaging among PWLWH in sub-Saharan Africa (SSA) and the potential to improve uptake of PMTCT services, clinic attendance and medication adherence [10][11][12][13][14]. Lay health workers, including mentor mothers, who provide psychosocial support to other PWLWH, have been utilized widely in SSA with improvements in uptake of PMTCT services, but have not been rigorously evaluated [15][16][17][18].…”
mentioning
confidence: 99%
“…Early studies have generally shown high acceptability of text messaging among PWLWH in sub-Saharan Africa (SSA) and the potential to improve uptake of PMTCT services, clinic attendance and medication adherence [10][11][12][13][14]. Lay health workers, including mentor mothers, who provide psychosocial support to other PWLWH, have been utilized widely in SSA with improvements in uptake of PMTCT services, but have not been rigorously evaluated [15][16][17][18].…”
mentioning
confidence: 99%
“…Researchers that used this framing positioned peers as logical interventionist to take up these roles, noting that patient navigation is generally performed by lay workers and paraprofessionals, and that peers possess qualities and experiences that may enhance their effectiveness [ 32 , 33 , 42 , 46 , 48 , 49 ]. Studies which did not explicitly conceptualise programs as peer or patient navigation [ 29 , 36 , 38 , 39 , 44 , 45 , 50 – 52 ] alternatively built on traditions of peer and lay health worker participation in health promotion for people living with HIV. These authors generally cited evidence that peer education and support are widespread in healthcare and that these interventions are effective for HIV prevention and improving clinical care outcomes for people living with HIV.…”
Section: Resultsmentioning
confidence: 99%
“…Our search identified research conducted in Mexico, India and seven countries in sub-Saharan Africa. The studies that we reviewed reported that intersecting forms of HIV-based stigma, discrimination, criminalisation, the high cost of healthcare and a lack of an enabling environment for key populations of women, sex workers, gay and bisexual men and men who have sex with men, people who use drugs, ethnic minorities and trans people were barriers to the effectiveness of peer navigation programs and health and wellbeing outcomes for people living with HIV [ 29 , 31 , 34 , 41 , 44 , 46 , 48 , 49 , 52 ]. No other studies targeted regions in which the HIV response has recently been identified as going backwards, such as Eastern Europe, Central Aisa, the Middle East, North Africa and Latin America [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is contrary to the assumption that all MMs had overcome (self)-stigma and were therefore willing and unafraid to disclose their HIV status. We have published detailed ndings on MM non-disclosure from the same Nigerian study setting [38].…”
Section: Discussionmentioning
confidence: 99%